2009
DOI: 10.1111/j.1468-3083.2009.03120.x
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of both persistent eczema and implant failure following removal of nickel containing implant

Abstract: References1 García FR, Paz RC, González RS et al. Cutaneous infection caused by Serratia marcescens in a child. J Am Acad Dermatol 2006; 55: 357-358. 2 João AM, Serrano PN, Cachão MP et al. Recurrent Serratia marcescens cutaneous infection manifesting as painful nodules and ulcers. J Am Acad Dermatol 2008; 58: S55-S57. 3 Epstein E, Carson TE. Serratia granuloma. JAMA 1973; 223: 670-671. 4 Marzano AV, Gasparini G, Caputo R. Cutaneous infection caused by Serratia marcescens. Cutis 2000; 66: 461-463. 5 Curtis CE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…During the course of the skin disease, this patient also developed clinical evidence of metal sensitivity. 130 Averbeck et al 112 suggested that patch tests might be false-negative if the implant material is located some distance from the skin. A biopsy of peri-implant tissue followed by a study of the T-cell infiltrate may be necessary in order to diagnose sensitivity to the implant material.…”
Section: Joint Replacementmentioning
confidence: 99%
See 1 more Smart Citation
“…During the course of the skin disease, this patient also developed clinical evidence of metal sensitivity. 130 Averbeck et al 112 suggested that patch tests might be false-negative if the implant material is located some distance from the skin. A biopsy of peri-implant tissue followed by a study of the T-cell infiltrate may be necessary in order to diagnose sensitivity to the implant material.…”
Section: Joint Replacementmentioning
confidence: 99%
“…Case reports have shown that nickel in spongiosa screws, 112 in a sacral stimulator, 113 in catheters for intravenous infusions, and in an eyelet in an intravenous catheter 114,115 may have caused systemic contact dermatitis.…”
Section: Joint Replacementmentioning
confidence: 99%